Influence of Parent Stressors on Adolescent Obesity in African American Youth - Lauren Allport; MinKyoung Song; Cindy W. Leung; Kellye C. McGlumphy; Rebecca E. Hasson (Hindawi Limited, 2019)
Objective. The purpose of this study was to examine the relationships between individual parent stressors (financial, legal, career, relationships, home safety, community safety, medical, housing, authority, and prejudice) and adolescent obesity in African American adolescents. Methods. Data were from a cross section convenience sample of 273 African American parent-child dyads (ages 11-19) from Washtenaw County, Michigan. A subset of 122 dyads who completed parent and child questionnaires were included in this analysis. Parent stressors were assessed using the Crisis in Family Systems Revised (CRISYS-R) questionnaire. Height, weight, and waist circumference were measured by trained staff; height and weight were converted to BMI. Multivariate linear regression models were used to examine the relationships between individual parent stressors and adolescent BMI and waist circumference. Results. Parental exposure to stressors related to safety in the community was positively associated with adolescent BMI (β = 1.20(0.47), p=0.01) and waist circumference (β = 2.86(1.18), p=0.02). Parental appraisal of stressors related to safety in the community as "difficult to get through" was positively associated with adolescent BMI (β = 0.39(0.14), p=0.006) and waist circumference (β = 1.00(0.35), p=0.005). These relationships remained significant when adjusting for behavioral and psychosocial covariates. There were no significant relationships observed between other parent stressors and adolescent BMI or waist circumference. Conclusion. These findings suggest parents' exposure and appraisal of stressors related to community safety are associated with increased adolescent obesity in African American youth. Longitudinal, larger-scale studies are needed to better understand the mechanisms by which community safety may increase obesity risk in this ethnic minority pediatric population. This trail is registered with NCT02938663.